(untitled) (Orinoquia, 2016)
Solid state fermentation (SSF) has become an alternative for animal feed; this biotechnological process means that harvesting residues and agro-industrial waste can be converted into energy-providing-protein-based feed having high nutritional value which, at any given moment, will totally or partially substitute balanced foods which significantly increase production costs, making livestock farms less profitable. SSF thus becomes not just an economically viable alternative but also an environmentally sustainable one by managing residues having highly contaminating potential. This review has been aimed at highlighting SSF as a biotechnological alternative for obtaining feed which can be used in animal production.